Comparison between objective measures and parental behavioral rating scales of memory and attention in pediatric endocrinology patients. Issue 2 (3rd April 2017) - Limbers, Christine; Young, Danielle; Jernigan, Stephanie; Bryant, William; Stephen, Matt
ABSTRACT: Behavioral rating scales represent one potential method for screening of cognitive functioning in routine clinical care. It is not yet known if objective performance based measures and behavioral rating scales of cognitive functioning completed by parents yield similar information in pediatric endocrinology patients. The purpose of the present study was to evaluate the associations between performance-based measures and behavioral rating scales of memory and attention/concentration completed by parents of pediatric patients with Type 1 Diabetes or obesity. The sample consisted of 73 pediatric patients with Type 1 Diabetes or obesity (BMI > 95th percentile) ages 6–16 years (mean age = 12.29 years) referred to an outpatient pediatric endocrinology clinic. Youth were administered the Wide Range Assessment of Memory and Learning (WRAML-2). Parents completed the Child Behavior Checklist (CBCL) and the PedsQL Cognitive Functioning Scale. Pearson's Product Moment Correlations were examined among the performance-based measures and behavioral rating scales. Results: All intercorrelations between the performance-based measures and behavioral rating scales completed by parents were in the small range. The only statistically significant ( P  < 0.05) and approaching medium correlation was between the PedsQL Cognitive Functioning Scale and WRAML-2 Verbal Memory Index ( r  = 0.28). On behavioral rating scales and performance-based measures of visual memory and attention/concentration, our sample exhibited greater difficulties than healthy youth from previously published data ( P  < 0.05). One possible explanation for our findings is that behavioral rating scales of attention/concentration and memory completed by parents measure different aspects of cognitive functioning than performance based measures in pediatric patients with Type 1 Diabetes or obesity.